(3GdOQI GdeVjI hGdYQhS GdeQVjI hGdTLQI GdfHhjI GdoeMeOjIs - (3jhSa Hf MSf Hf CMeO Hf MSf Hf YHO GdgGOj GdUGdMj, LeGd GdOjf, GHf GdeHQO,J (B909 (3g` s ((3TeS GdOjf GjhHj Hf SjO eMehO HZOGOj s)
(3BNQgG (B:s
(3NdGaI YeQ Hf YHOGdYRjR SfI EMOi heGFI, heOJg SfJGf hNeSI CTgQ s
(3fSNI KGfjIs
(3GdUaMI GdChdi eeRbIs
(3hHgG BKGQ WeSs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs